Intercontinental comparison of patient cohorts: what can we learn from it?. Issue 11 (15th October 2007) - Schemmer, P; Fischer, L; Schmidt, J; Büchler, M W
Abstract : Survival after liver transplantation in the United Kingdom and Ireland compared with the United States